The dominant influence of indian ocean dipole-like ocean warming on decreased precipitation over eastern East Antarctica - Lee, Hyun-Ju; Jin, Emilia Kyung (Frontiers in Earth Science, 2024)
East Antarctica is undergoing a noticeable decrease in precipitation, significantly impacting ice mass loss. However, there is a lack of research on the underlying factors behind this change. This study highlights that on an interannual timescale, the precipitation variations in Eastern East Antarctic (EEA) are predominantly influenced by the Indian Ocean Dipole mode (IOD) compared to other climate variabilities like the Southern Annual Mode (SAM), El Niño-Southern Oscillation (ENSO), and north Atlantic variability. Through trend analysis of each climate variability, we confirmed that the observed decrease in EEA precipitation can be attributed to positive IOD-like ocean warming. A positive SAM trend also contributed to specific Wilkes Land and Queen Mary Land regions. Despite these influence on long-term trend, the relationship between IOD and EEA precipitation exhibits sporadic changes on interdecadal timescales. Notably, the apparent negative correlation between the two declined to insignificance in the early 2000s, only to re-establish a significant negative correlation by the early 2010s. The primary driver of this change is the inconsistent propagation of waves originating from the Indian Ocean. During periods of high correlation, these waves propagate southeastward, inducing a robust low-pressure anomaly near Victoria Land, ultimately leading to decreased EEA precipitation. However, during periods of low correlation, the waves move eastward and fail to alter the circulation anomalies near East Antarctica. Keywords: Eastern East Antarctica (EEA), Decreased precipitation trend in EEA, Positive IOD-like ocean warming, Interdecadal change in the relationship between IOD and EEA precipitation, Changes in teleconnections